Exploring collaborative governance and community participation in tourism and conservation—insights from Waiheke Island, New Zealand - Mahmoud Sarhan; Tomas Pernecky; Mark Orams; Michael Lück (Frontiers in Sustainable Tourism)
IntroductionBalancing conservation efforts with tourism development poses significant challenges in Small islands. Waiheke Island, located in New Zealand's inner Hauraki Gulf, is both a popular residential location and a popular tourism destination facing similar challenges in governing tourism and conservation. This study examined the characteristics of the local residential community, conservation and tourism governance, the environmental and social impacts of tourism, and nature conservation efforts on the island.MethodsA qualitative case study approach was employed, involving interviews with stakeholders, field observation and review of secondary data sources. The research explored governance complexities, power imbalances, and stakeholder dynamics that shape community participation in tourism and conservation decision-making.Results and discussionThe findings reveal a complex governance landscape marked by both strengths and challenges. The research highlights the pivotal role of community-driven governance, with grassroots initiatives demonstrating remarkable adaptive capacity in addressing governance gaps. The Waiheke Local Board emerged as a crucial mediator between competing interests, while the integration of Māori perspectives through documents like Essentially Waiheke reflects growing recognition of indigenous knowledge systems. However, the study also uncovers tensions, including fragmented decision-making where regional authorities override local preferences, and the need for further inclusion of local views on governance. The current governance system, which is influenced by the environmental-socioeconomic dynamics, creates a paradox where effective actors (such as grassroots initiatives/groups and tourism actors) lack appropriate inclusion in decision-making, while regional bodies retain decision-making power. The island's hybrid governance structure, blending formal institutions with informal networks, provides stability but requires more equitable power distribution to be fully effective. While collaborative efforts show promise, they are undermined by bureaucratic hurdles, inconsistent government support, and insufficient community engagement. The study proposes a framework for enhanced collaborative governance through strengthening local autonomy, formalizing co-governance arrangements, better supporting grassroots initiatives, and developing a community-driven destination management plan. These recommendations aim to reconcile the island's formal-informal governance duality while balancing tourism growth with environmental conservation and community wellbeing. The findings offer insights for other small islands facing similar governance challenges at the intersection of conservation and tourism development.